Habituation of Religious Character Based on Al-Islam and Kemuhammadiyahan in Elementary Schools - Izzatur Rosuli; Muhlasin Amrullah (Journal of Islamic and Muhammadiyah Studies, 2023)
This study aims to determine the habituation of religious character based on Al Islam and Kemuhammadiyahan in Elementary School. The research method uses a descriptive qualitative approach, wherea data collected is data in the form of words, images, and not numbers. The data collection techniques used by researchers are triangulation techniques, namely observation, interviews, and documentation. In this study, researchers found that at SD Muhammadiyah 1 Wringinanom, they used to a religious character based on Al Islam and Kemuhammadiyahan. There are supporting and inhibiting factors in its implementation. The supporting factors are the support of parents, the joint commitment of school residents, adequate facilities. The inhibiting factors are the different backgrounds of students, the social environment of students, and the lack of awareness of students.